Environmental and coastline changes controlling Holocene carbon accumulation rates in fjords of the western Strait of Magellan region. (1st August 2020) - Ríos, Francisco; Kilian, Rolf; Lange, Carina B.; Baeza-Urrea, Oscar; Arz, Helge W.; Zindorf, Mark; De Pol-Holz, Ricardo; Lamy, Frank
Abstract: Organic-rich sediments of the southernmost Chilean Pacific coast and its fjord system constitute an important component of the global marine carbon budget. Sediment records from Trampa and Caribe bays and Churruca fjord in the western Magellan fjord system have been analyzed with the goal of understanding the factors controlling carbon accumulation and its regional fluctuation throughout the Holocene. The individual response in paleoproductivity at the different sites and related variations in accumulation rates document a very complex interplay among local and regional-scale environmental changes, and coastline elevation across the Holocene. Shallow sill basins close to the Pacific coast, as the ones studied here, are particularly sensitive to these processes, having responded with strong productivity changes throughout the Holocene. A Bayesian mixed model approach, using sediment archived provenance proxies, indicates that components of terrestrial plants and soils washed-out into these basins contribute with a variable proportion (20–80 wt%) of the total accumulated organic carbon. Accumulation rates of terrestrial carbon increase with the amount of precipitation in the hyper-humid mountain area, but also reflect distinct Holocene plant successions as well as long-term development of soil and vegetation cover that strongly overprint the direct precipitation impact. Over the Holocene accumulation rates of biogenic carbonate and aquatic-marine organic carbon range between 5 and 118 kg m −2 kyr −1 and 0.3–20 kg m −2 kyr −1, respectively. This variability depends on water column structure and conditions, which are regulated by the degree of marine transgression as a function of post glacial sea level rise and isostatic uplift as well as precipitation-related surface water freshening. In the Bahia Trampa record, a significant change in accumulation rates indicates a marine transgression at ca. 12.2 kyr BP, when the global sea level was 60–70 m lower than today and eustatic rise overcame isostatic rebound rates. In Caribe and Trampa records, CaCO3 accumulation rates were higher at ca. 7 kyr BP. The Churruca record shows organic carbon accumulation rates up to 36.2 kg m −2 kyr −1 during the early Holocene. Highlights: Holocene sediment records from coastal siltes with shallow sites in the western Patagonian fjord system are presented. Local environmental conditons strongly affect Holocene accumulation rates of terrestrial carbon in Patagonian fjords. Sea level variations and isostatic adjustments control marine organic carbon and CaCO3 accumulation rates. The timing and magnitude of the marine transgression is controlled by the specific sill depth at each studied site.